A Trauma-Informed Care Framework for Early Childhood Behavioral Interventions in Underserved Communities - Augustine Onyeka Okoli,; Opeoluwa Oluwanifemi Akomolafe,; Damilola Oluyemi Merotiwon,; Erica Afrihyia, (International Journal of Scientific Research in Science and Technology, 2025)
This paper proposes a trauma-informed care (TIC) framework for early childhood behavioral interventions in underserved communities, emphasizing the importance of understanding and addressing the impacts of trauma on young children’s development. The framework advocates for a holistic approach, integrating trauma awareness, safety, and resilience-building strategies into early childhood education and behavioral health services. By recognizing the prevalence of adverse childhood experiences (ACEs) in marginalized populations, this model seeks to mitigate the long-term effects of trauma on emotional, cognitive, and social functioning. Through trauma-informed practices, educators, caregivers, and healthcare providers can create supportive, nurturing environments that foster healing and development. The paper explores the challenges faced by underserved communities, such as limited resources, cultural barriers, and systemic inequities, and presents strategies to overcome these obstacles through community-driven solutions. This framework aims to empower both practitioners and families, promoting sustainable and culturally relevant interventions that enhance the overall well-being of children in these communities.
Keywords: Behavioral health; resilience; emotional development; early childhood education; cultural relevance